Long-range attraction between charge-mosaic surfaces across water. - Perkin, S; Kampf, N; Klein, J (2006)
We have measured directly the forces across water between hydrophilic surfaces covered with a random mosaic of positive and negative charged domains. We find a strong, long-ranged attraction between them at a surface separation comparable with the charge domain size (many tens of nanometers). This attraction persists at higher salt concentration, but its range then becomes comparable to the Debye screening length. We attribute the attraction to correlation between negative and positive regions on opposing surfaces, facilitated by the lateral mobility of the charge patches on the surfaces.